Utilization of Tongkah in the Productivity of Shellfish Fishermen in Tembeling Village, Bintan Regency - Nurhasanah Nurhasanah; Saddam Bintang Juang; Fhazli Maulana Ikhsan; Maisya Tusaqdiah; Zaria Tasya; Lingga Aulya Mayori (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study analyzes the tongkah, a traditional sliding board, to enhance shellfish fishermen productivity in Tembeling Village, Bintan Regency. Methodology/approach: This study employed a qualitative case study approach conducted in Tembeling Village, Riau Islands, Indonesia. Data were collected through participatory observation, in-depth interviews, and documentation involving shellfish fishermen and key community informants selected through purposive sampling methods. Results/findings: The findings show that tongkah increases fishermen's productivity by reducing operational costs, shortening harvesting time, and expanding access to fishing areas that small boats cannot reach during low tide. In addition to its economic benefits, tongkah reflects local wisdom by strengthening cultural identity, social solidarity, and intergenerational knowledge transfer. Sustainability challenges include the limited availability of pulai wood, environmental change, extreme weather, and potential coastal development policies. Conclusions: The use of tongkah enhances the productivity of shellfish fishermen in Tembeling through improved efficiency and spatial access, while simultaneously supporting sociocultural values. Long-term sustainability requires adaptive innovation and supportive coastal management policy. Limitations: The study is limited to a single village, uses a qualitative descriptive method without quantitative productivity measures, and may be subject to subjective bias despite triangulation. External factors, such as coastal policies and climate change, were not examined in depth. Contributions: This study provides empirical evidence that traditional tools can bolster the livelihoods of small-scale coastal fishers and links tongkah use to productivity within frameworks such as Sustainable Livelihoods and cultural economics, informing fisheries science, coastal economics, and resource management.